2009
DOI: 10.2164/jandrol.108.006015
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Link Between Hypogonadism and Metabolic Syndrome

Abstract: The metabolic syndrome (MS) is comprised of various medical conditions that confer increased risk of diabetes and cardiovascular disease. The pathophysiologic components of MS include glucose abnormality, obesity or increased waist circumference, increased blood pressure, and hyperlipidemia. There is an increased risk of hypogonadism in men with MS and its individual components, including insulin resistance, considered by some to be at the core of MS. Hypogonadism may even predict MS. These factors are interwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 56 publications
1
26
0
3
Order By: Relevance
“…There seems to be an interrelationship between hypogonadism and MS (25). Several cross-sectional studies report increased prevalence of hypogonadism in MS (8, 9, 11), while many others report increased prevalence of MS and diabetes mellitus in subjects with lower testosterone levels (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There seems to be an interrelationship between hypogonadism and MS (25). Several cross-sectional studies report increased prevalence of hypogonadism in MS (8, 9, 11), while many others report increased prevalence of MS and diabetes mellitus in subjects with lower testosterone levels (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data are noteworthy as they show poor metabolic parameters in a sizeable group of treatment-naïve patients with CHH, mentioning that hypogonadism can cause MS even in very young ages. Testosterone replacement is expected to improve the metabolic abnormalities in patients with hypogonadism (25), and for some authors, it may be a novel treatment option in MS (26). However, reports about the metabolic effects of testosterone replacement are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between the metabolic syndrome and hypogonadism has been suggested (Guay et al, 2009) and it has been shown that nearly all aspects of the metabolic syndrome are associated with reduced testosterone levels (Phillips et al, 2003;Svartberg et al, 2004;Stellato et al, 2000). A crosssectional study showed that men with low testosterone levels have a higher prevalence of metabolic syndrome (Muller et al, 2005).…”
Section: Hypogonadism Metabolic Syndrome and Prostate Cancermentioning
confidence: 99%
“…Na população geral, a deficiência androgêni-ca pode contribuir para o surgimento de alterações no perfil glicídico e lipídico (16). Em obesos, níveis séricos de testosterona se correlacionam inversamente com a obesidade visceral, a síndrome metabólica, a resistência à insulina (17), a hipertensão arterial, os níveis baixos de HDL-c e a hipertrigliceridemia (18).…”
Section: Discussionunclassified